THE HALOPHYTE PLANT RESOURCES OF THE FOREDUNES ON THE SOUTH-CENTRAL COAST OF VIETNAM - Ba Le Le; Van Binh Nguyen; Thi Lan Anh Truong; Khoa Truong Nguyen; Thai Vinh Tran; Hoang Nghia Nguyen; Van Hoi Quach; Van Giang Nguyen; Hoang Dai Phan; Thi Kim Ngan Le; Thi Ai Minh Nguyen; Truong Thanh Hoang; et al. (Tạp chí Khoa học Đại học Đà Lạt)
Halophytic plant resources play a vital role in meeting the needs of local people, and they have potential applications in nutrition and sustainable agriculture. Ethnobotanical surveys were conducted on foredunes at 41 study sites in 8 provinces of the south-central coastal region of Vietnam. The findings show that the majority of halophytic plants fall into the following resource groups: traditional medicine (45.13%, 88 species), food, (13.85%, 27 species), woody plants (4.62%, 9 species), and ornamentals (4.10%, 8 species). In comparison, 26.67% (54 species) have not been documented for specific uses. Halophytic resources account for 73.34% of the surveyed species, highlighting their significant ethnobotanical value. Cultivating these natural resources can benefit coastal communities by supporting local socio-economic development while promoting the environmental sustainability of the coastal soils and climate.